Application of Integrated Geophysical Methods for Groundwater Exploration in Iworoko-Ekiti, Southwestern Nigeria - Adeoye, Aderemi Sunday; Ajayi, Christopher Ayodele; Ibrahim , Olanrewaju Ibrahim (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
Electrical Resistivity and Electromagnetic Methods were adopted to probe the subsurface formation of the Isaba Garri processing Industry environment as a result of challenges experienced in groundwater production. The environment falls on a big outcrop of land where proximity of locating a position for a borehole has been difficult. The Impact method, Electromagnetic method using gradient array method and Three Vertical Electrical Soundings were established along a single 120 m traverse orientated in a north-south direction. The Electromagnetic approach served as a pre-study for the establishment of the VES. The EM and VES methods revealed different geologic formations which are; topsoil, weathered layer, fresh basement and fractured basement with resistivity range of 96 – 976, 1396 – 2380, 4546 – 28594 and 126 ohm-m, and thicknesses range of 1.2 – 2.9, 5.3 – 6.2, 4.1 to infinity and 10.7 m respectively. The result revealed that VES 1 located at the southern part of the study, is good enough for borehole drilling for the successful running of the Industry.